Intrinsic fluorescence of selenium nanoparticles for cellular imaging applications. Issue 6 (21st January 2016) - Khalid, A.; Tran, Phong A.; Norello, Romina; Simpson, David A.; O'Connor, Andrea J.; Tomljenovic-Hanic, Snjezana
Abstract : (a) Microscopic image of selenium nanoparticles uptaken by the fibroblast cells. (b) Intrinsic fluorescence of the particles exploited for in vitro imaging. Abstract : Nanoparticles hold great potential in contributing to high-resolution bioimaging as well as for biomedical applications. Although, selenium (Se) nanoparticles (NPs) have been investigated owing to their potential roles in therapeutics, the imaging capability of these NPs has never been explored. This manuscript identifies the intrinsic fluorescence of Se NPs, which is highly beneficial for nanoscale imaging of biological structures. The emission of individual NPs and its evolution with time is explored. The photoluminescence spectra has revealed visible to near infrared emission for Se NPs. The work finally reflects on the role of this intrinsic fluorescence for in vitro imaging and tracking in fibroblast cells, without the need of any additional tags. This technique would overcome the limitations of the conventionally used methods of imaging with tagged fluorescent proteins and dyes, preventing possible adverse cellular effects or phototoxicity caused by the added fluorescent moieties.